Apigenin as a multifaceted antifibrotic agent: Therapeutic potential across organ systems - Xiaoyong Hu; Djandan Tadum Arthur Vithran; Zhaoying Yang; Ting Zou; Yuanyuan Dou; Hongjian Li (Journal of Agriculture and Food Research)
Fibrosis, characterized by excessive extracellular matrix (ECM) deposition, leads to tissue scarring and organ dysfunction in various conditions affecting the heart, lungs, pancreas, kidneys, bones, and joints. Despite its significant impact on global morbidity and mortality, effective antifibrotic treatments remain limited. Apigenin, a plant-derived flavonoid found in common sources such as parsley, chamomile, and celery, has garnered attention for its potent antifibrotic, antioxidant, and anti-inflammatory effects. This narrative review provides a focused analysis of apigenin's role in mitigating fibrosis across multiple organ systems, emphasizing its mechanistic pathways and therapeutic potential.Apigenin's antifibrotic effects are highlighted in key organs. In cardiac fibrosis, it inhibits TGF-β1-induced fibroblast activation, modulates microRNAs (miR-155-5p, miR-122-5p), and downregulates hypoxia-inducible factor-1α (HIF-1α), reducing ECM deposition. In pulmonary fibrosis, apigenin attenuates oxidative stress, suppresses fibroblast activation, and reduces collagen accumulation, improving lung function. It also demonstrates protective effects in pancreatic and renal fibrosis by reducing oxidative damage and inflammation. In bone and joint fibrosis, apigenin enhances bone remodeling and mitigates joint inflammation, promising to manage osteoarthritis and related conditions.This review uniquely consolidates evidence of apigenin's antifibrotic properties across diverse organ systems, positioning it as a promising candidate for treating fibrotic diseases. Continued research is essential to explore its clinical applications and long-term efficacy.